The Effect of Training on Improving the Quality of Medical Services in Saudi Arabia's Hospitals. Practical Study on King Abedallah Hospital-Bisha Province - Mousi, Abdul Rahim Abbas (Journal of Economic, Administrative and Legal Sciences, 2019)
The Study aimed at identifying the effect of training on improving the quality of medical services in Saudi Arabia's hospital-king Abedellah as an example. The study was implemented on a sample from medical doctors ,the administrators, and the assisting medical carders. The descriptive analytical approach was used as a questionnaire was designed for data collection. Seventy (70) copies were distributed (65)were recollected and valid for analysis. Number of statistical methods were used, like the mean, the standard deviation, Alfa Cornbakh, Person correlation and the analysis of the deviation. The findings proved that improvement and up-dating in the activities of training are not considered. The due medical specializations are not available. The quality of training will be positively reflected on the quality of the medical services provided by the hospital. The trainers and trainees ensured that training led to the improvement of the quality of medical services. The study ensured that the ways of training are various and up-to date. The study recommended that the decision of the training needs should be based on scientific basis. Preparation of training and orientation programs should be around the concepts of quality and the comprehensive quality. Conduction of more researches concerning training on other sectors of services due to its significance and effectiveness on the quality of services provided by the hospitals. The process of training should be pushed on by incentives in cash or wording.
Keywords: Training; improvement of quality of services; King Abedallah Hospital